THE MOST COMMON DISORDERS OF THE HAND ASSOCIATED WITH CARPAL TUNNEL SYNDROME IN ADULTS - Dushanka Grujoska Veta; Daniela Georgieva; Atanasov, Nenad; Ilir Shabani; Liljana Angeleska; Antonio Georgiev; Jasna Bogdanska (Институт за јавно здравје на Република Македонија = Institute of public health of Republic of Macedonia, 2021)
Carpal tunnel syndrome (CTS) is one of the most common peripheral neuropathies caused by chronic compression of the median nerve in the area of the carpal tunnel and its etiology is multifactorial. Trigger fingers and de Quervain’s disease are common disorders of the hand related to CTS in adults.Theaim of this study was to present the most common disorders of the hand such as stenosing tenosynovitis in adults with surgically treated CTS and to evaluate their demographic data.Material and methods: A total of 116 surgically treated patients with established diagnosis of CTS (clinically and by electrophysiological examination) were included in this prospective study, which was conducted at the University Clinic for Orthopedic Diseases in Skopje. Demographic data, findings of history of the disease and clinical examination were recorded and analyzed.Results: Participants with CTS included in the study were with a mean age of 55.41±10.7 years (age range 29-75). 75% of them were female. 63.8% of participants suffered from one or more comorbid chronic diseases. On admission to hospital, disorders such as trigger fingers and de Quervain’s disease were concomitantly diagnosed in 15.51% on ipsilateral hand with CTS. All disorders were surgically treated following open carpal tunnel release, as “one stage procedure”, under local anesthesia.Conclusion: Our findings have determined concomitant existence of CTS and stenosing tenosynovitis (trigger fingers and de Quervain’s disease) on ipsilateral hand, which suggests common etiological factors. Female gender and age range 40-60 years are major common factors related to these three disorders.